Website Design in Property - B Kurniawan; C Leonardo; S Alviana (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this research is to design a home purchases website to make a transaction easier. This research was conducted using quantitative research method and literature studies from various journals. The result from this study is that building the home purchase websites make the consumer gets the information faster and easier. The website design is expected to help people to do a transaction in Bandung.